Environmental variability and governance: The fishery of Octopus maya in Yucatan, Mexico - Santamaría, Antonio; Euán Ávila, Jorge I.; Munguia-Rosas, Miguel A.; Saldívar-Lucio, Romeo; Fraga, Julia (Frontiers in Marine Science, 2023)
In the socio-ecological system of the Mayan octopus, climate change, natural variability and human decisions impact the dynamics and population structure of the octopus. Since fishing decisions have been made out of synchrony concerning the octopus’s natural response, the system’s sustainability is put at risk. Sustainability is a socially desirable, environmentally necessary, and economically viable goal; since it contributes positively to food security, ways, and lifestyles. The objective of this work is to deepen the study of the perception of the fishermen of Progreso, Yucatán regarding the interactions between the Mayan octopus, the variability in the environment, the governance system, and fishing decisions. It was developed from a qualitative and quantitative approach, and bonds of trust were created for a year adopting an ethnographic approach to deepen the use of language, feelings, and emotions. To obtain information, open and semi-structured interviews, participant observation, and documentary research were carried out. For the analysis and evaluation of perceptions and fishing decisions, a non-parametric test was used through the modeling of structural equations with Partial Least Squares (PLS). It was found that, although the quantity to be captured is strongly influenced by the market, the strong incidence of changes in the environment on capture decisions stands out among the results. The experiences and knowledge of the fishermen about the marine environment represent an opportunity to contribute to the process of evolution of the socio-ecological system of the Mayan octopus, towards the establishment of norms and agreements between the different actors and contribute to the construction of resilience and sustainability against the overexploitation and environmental variability.